A comparative study of dc–dc converters' effects on the output characteristics of direct ethanol fuel cells and NiCd batteries - Misoc, Florian (Kansas State University, 2007)
Characterized by variable impedances, DC power sources normal operation, reliability, and life-time is negatively affected by the sequential switching within any DC power system. The impedances of Nickel-Cadmium (NiCd) storage batteries and Direct Ethanol Fuel Cells (DEFC) vary nonlinearly; therefore, existing DC power system models, that employ averaging of the sequential switching process, are inaccurate in describing the system output voltage. In this research, Fourier-series models of DC–DC converters are developed and evaluated, through numerical computations and computer simulations. Both NiCd-DC converter and DEFC-DC converter power systems are experimentally evaluated over a selected switching frequency range. Input voltage and output voltage characteristics of two types of DEFC-DC converter systems (Nickel-mesh and Nickel-foam electrode assembly) are determined. Experimental results are compared to computer simulations, thus validating the Fourier-series models. Experimental results show a correlation between the DC converter switching frequency and the output of the DC power system. Sequential switching operation, along with the type of DC converter employed, are factors determining the maximum power transfer of the system. The models developed in this work are flexible over a large switching frequency range, and for any desired duty cycle. Correction factors, accounting for the source-converter impedance matching, are easily implemented in Fourier-series models. The research demonstrates the advantages of Fourier-series models, as compared to both large-signal and small-signal models, with regard to accuracy and ease of implementation to any DC–DC converter-driven power system.
Keywords: DC–DC converter; direct ethanol fuel cell; Engineering, Electronics and Electrical (0544)